"As long as there's no mortal risk": the perspectives of members in combat arms occupations on children's outdoor risky play. Issue 7 (23rd November 2022) - Bauer, Michelle E. E.; Giles, Audrey R.; Brussoni, Mariana
ABSTRACT: Parents' experiences with risk can influence their perspectives on their children's outdoor risky play. Parents in combat arms occupations in the Canadian Armed Forces have unique experiences with risk, as their occupations regularly include encountering and successfully navigating risky environments in military operations. In this study, we conducted seven semi-structured interviews with parents in combat arms occupations and used risk and sociocultural theory. Our reflexive thematic analysis resulted in two main findings: (1) Members believed outdoor risky play was beneficial for children to experience and supported children's engagement in it; and (2) members distinguished between children's outdoor risky play-related non-serious and serious injuries. Our findings advance scholarly conversations on how risk may be perceived and negotiated more broadly in populations who engage with risk on a frequent basis.